HuD Binds to and Regulates Circular RNAs Derived From Neuronal Development- and Synaptic Plasticity-Associated Genes - Dell’Orco, Michela; Oliver, Robert J.; Perrone-Bizzozero, Nora (Frontiers in Genetics, 2020)
The RNA-binding protein (RBP) HuD is involved in neuronal differentiation, regeneration, synaptic plasticity and learning and memory. RBPs not only bind to mRNAs but also interact with several types of RNAs including circular RNAs (circRNAs), a class of non-coding RNAs generated by pre-mRNA back-splicing. This study explored whether HuD could regulate the expression of neuronal circRNAs. HuD controls target RNA’s fate by binding to Adenylate-Uridylate Rich Elements (AREs). Using bioinformatics analyses, we found HuD-binding ARE-motifs in about 26% of brain-expressed circRNAs. By RNA immunoprecipitation (RIP) from the mouse striatum followed by circRNA arrays, we identified over 600 circRNAs bound to HuD. Among these, 226 derived from genes where HuD also bound to their associated mRNAs including circHomer1a, which we previously characterized as a synaptic HuD target circRNA. Binding of HuD to two additional plasticity–associated circRNAs, circCreb1, and circUfp2, was validated by circRNA-specific qRT-PCR. Interestingly, we found that circUpf2 is also enriched in synaptosomes. Pathway analyses confirmed that the majority of HuD-bound circRNAs originate from genes regulating nervous system development and function. Using striatal tissues from HuD overexpressor (HuD-OE) and knock out (KO) mice for circRNA expression analyses we identified 86 HuD-regulated circRNAs. These derived from genes within the same biological pathways as the HuD RIP. Cross-correlation analyses of HuD-regulated and HuD-bound circRNAs identified 69 regulated in either HuD-OE or HuD-KO and 5 in both sets. These include circBrwd1, circFoxp1, and circMap1a, which derive from genes involved in neuronal development and regeneration, and circMagi1 and circLppr4, originating from genes controlling synapse formation and linked to psychiatric disorders. These circRNAs form competing endogenous RNA (ceRNA) networks including microRNAs and mRNAs. Among the HuD target circRNAs, circBrwd1 and circFoxp1 are regulated in an opposite manner to their respective mRNAs. The expressions of other development- and plasticity-associated HuD target circRNAs such as circSatb2, cirHomer1a and circNtrk3 are also altered after the establishment of cocaine conditioned place preference (CPP). Collectively, these data suggest that HuD interactions with circRNAs regulate their expression and transport, and that the ensuing changes in HuD-regulated ceRNA networks could control neuronal differentiation and synaptic plasticity.